Abraham Lincoln : a biography - Thomas, Benjamin Platt, 1902-1956 (Southern Illinois University Press, 2008)
Long considered a classic, Benjamin P. Thomas's Abraham Lincoln: A Biography takes an incisive look at one of American history's greatest figures. Originally published in 1952 to wide acclaim, this eloquent account rises above previously romanticized depictions of the sixteenth president to reveal the real Lincoln: a complex, shrewd, and dynamic individual whose exceptional life has long intrigued the public. Thomas traces the president from his hardscrabble beginnings and early political career, through his years as an Illinois lawyer and his presidency during the Civil War. Although Lincol.